Low-Cost IoT Communication in the Arctic Region: Using the SWARM Satellite Constellation for Remote Community Connectivity - Anastasiya Yermolenko; Philip Ferguson (Aerospace, 2025)
The Arctic region is known for its harsh and remote environment. Some of the significant system problems in that region include solving communication issues and building a high-capacity terrestrial infrastructure. This study presents an innovative solution leveraging SWARM Technologies’ low-bandwidth satellite connectivity, Sustainable Distributed Cloud Infrastructure (HIVE) cloud, and devices that are used to develop an automated system for data transfer over any distance without reliance on the Internet. Using this technology, we constructed a solution that integrates SWARM devices with Amazon Web Services (AWS), utilizing an Application Programming Interface (API) for automated notification handling, data storage, and other key functionalities. This paper presented an innovative approach utilizing AWS and the HIVE cloud for easy communication and data transfer between the SWARM device and scientists around the world. This research will help provide a cost-effective method to address the issue of collecting and transferring any type of small data without the Internet in isolated areas like the Arctic region.